KEKERASAN RAGAWI TERHADAP TOKOH BIRU LAUT DALAM NOVEL LAUT BERCERITA : IMPLIKASI UNTUK KAMPANYE ANTIKEKERASAN - Laksana, Bela Tri; Ambarwati, Ari (Hiski Malang, 2022)
The purpose of this study is to describe the physical violence experienced by the character Biru Laut in the novel Laut Bercerita. This study used qualitative descriptive research method. The source of the data was obtained from direct quotes of conversations of Blue characters in the novel Sea of Storytelling. The findings showed that physical violence was divided into two types, namely (1) physiological violence that relies on physical conditions and, (2) anatomical violence such as kicking, pushing, slapping and so on. Bullying is an act of physical violence that must be avoided, not only harming 1 party but several parties also become victims. Bullying can be overcome by providing understanding to students through counseling guidance.The purpose of this study is to describe the physical violence experienced by the character Biru Laut in the novel Laut Bercerita. This study used qualitative descriptive research method. The source of the data was obtained from direct quotes of conversations of Blue characters in the novel Sea of Storytelling. The findings showed that physical violence was divided into two types, namely (1) physiological violence that relies on physical conditions and, (2) anatomical violence such as kicking, pushing, slapping and so on. Bullying is an act of physical violence that must be avoided, not only harming 1 party but several parties also become victims. Bullying can be overcome by providing understanding to students through counseling guidance.